HUBUNGAN PRESTASI PRAKTIK KERJA INDUSTRI DENGAN KESIAPAN KERJA SEKOLAH MENENGAH KEJURUAN - Ridhani, Rizki; Karyaningsih, Endang Wani (Universitas Sarjanawiyata Tamansiswa, 2024)
The purpose of this study was to determine (1) The relationship between industrial work practice performance and work readiness of students of class XI fashion at SMK Negeri 2 Godean, (2) work readiness of students fashion design, (3) achievement of industrial work practices students of fashion. This research belongs to the type of ex-post facto research. Methods of data collection using the method of questionnaires and documentation. The data analysis technique used descriptive analysis techniques and hypothesis testing using the Product Moment correlation test which was preceded by normality and linearity tests. The results showed that (1) There was a relationship between industrial work practice performance and work readiness of fashion students, the value of r count = 0.674 > rtable = 0.207. The coefficient of determinant (R2) is 0.334, meaning that the contribution given by the X variable to the Y variable is 45.4%, while the remaining 54.6% is influenced by other factors not discussed in this study. (2) Most of the students' work readiness is in the high category with a frequency of 63.44%. (3) Most of the students' industrial work practice achievements are in the high category with a relative frequency of 53.76%. Keyword: Achievement, Industrial Work Practice, Work Readiness.